Application of marker assisted selection for livestock improvement in Bangladesh (Bangladesh Veterinarian, 2015)
Molecular markers usually do not have any biological effect. They are identifiable DNA sequences, found at specific locations of the genome, and transmitted from one generation to the next. Marker assisted selection (MAS) is a novel technique that can complement traditional breeding methods for rapid genetic gains. Genetic gain through selective breeding is the objective of a breeder to achieve long term improvement in animal and plant genomes; however the pace of improvement is inversely proportional to the Generation Interval. Genetic improvement in livestock, particularly those with long generation intervals, requires decades for tangible results. Successful MAS breeding programmes require gene mapping, marker genotyping, quantitative trait loci (QTL) detection, genetic evaluation and finally MAS. Genomic selection is a form of markerassisted selection. Using markers covering the whole genome could mean potentially that all the genetic variance is explained; and the markers are assumed to be in linkage disequilibrium with the QTL so that the number of effects per QTL to be estimated is small. MAS drastically reduces generation interval and increases selection accuracy. Therefore, a breeding strategy based upon markers making the best use of the two approaches can facilitate rapid genetic gain though selection of markers related to economic traits such as milk and meat production. This review is designed to elaborate the technique of MAS and its application in developing countries. DOI: http://dx.doi.org/10.3329/bvet.v31i1.22837 Bangl. vet. 2014. Vol. 31, No. 1, 1-11